The histamine content of rabbit leucocytes and its release during in vitro anaphylaxis - Greaves, M. W. (1968)
A method has been devised for obtaining from rabbit blood suspensions of leucocytes rich in basophils but depleted of platelets. The preparation contains histamine equivalent to 0·2 μg/ml of blood or 1·3 pg/basophil. In vitro anaphylactic histamine release by suspensions obtained from actively sensitized rabbits has been demonstrated and some properties of this new system have been described.